Investigation of the effects of silymarin and vitamin C on kidney damage and aquaporin-2 downregulation in lithium-induced nephrogenic diabetes insipidus in rats - Yakut, Seda; Gencer, Berrin Tarakci; Yalcin, Mehmet Hanifi; Aydin, Suleyman; Yuksel, Hayati (Taylor & Francis Ltd, 2025)
Although lithium (LIT) therapy is key in managing bipolar disorder long-term, prolonged use significantly contributes to acquired Nephrogenic Diabetes Insipidus (NDI). This study examined whether combining Silymarin (SIL) with Vitamin C (Vit C) enhances protection against lithium-induced nephrotoxicity in rats, comparing their individual antioxidant effects as well. Rats subjected to Li exposure were provided with a standard commercial diet supplemented with 80 mmol LiCl per kilogram for 28 days. Concurrently, SIL and Vit C were administered orally at dosages of 200 and 100 mg/kg body weight, respectively, throughout the 28 days. The study assessed levels of reactive oxygen species (ROS), glutathione (GSH), and malondialdehyde (MDA), as well as the enzyme activity of superoxide dismutase (SOD), to evaluate the protective effects of SIL and Vit C against oxidative stress. Aquaporin-2 (AQP2) levels in kidney tissues were evaluated using immunohistochemistry and ELISA. Serum and urine parameters (sodium, potassium, creatinine, blood urea nitrogen [BUN], and urea) and serum lithium levels were also measured. Lithium-induced nephrotoxicity showed increased renal toxicity markers and decreased antioxidant enzyme activity. SIL administration significantly reduced markers of kidney tissue toxicity, increased antioxidant enzyme activities, regulated the aforementioned physiological parameters in blood and urine, and downregulated AQP2 expression in the kidney. However, Vit C administration did not demonstrate a significant protective effect against lithium-induced renal toxicity. These findings indicate that SIL effectively protects against lithium-induced nephrotoxicity, whereas Vitamin C does not exhibit this protective effect.
Keywords: Lithium; nephrogenic diabetes insipidus; AQP2; silymarin; vitamin C